Evaluación del proceso productivo de Mermeladas en la Asociación ASOPRUV. - Espinosa Gallardo, Rommel Vinicio (2018)
The research project is focus on evaluate and analyze the jam production and elaboration process in the ASOPRUV association, which does not have a technical productive organization and whose processes, methods and time are not standardized; in addition, the distribution of the machinery in the plant is not established in a suitable way, as a result which makes the process of production has low levels, and also the factory permanence as competitive factory in the Ecuadorian market is in risk. The evaluation and analysis was realized with the previous information was generated with the actual situation by applying a fiel research, the producer involves the identification of the products and its elaboration process, for this a flow chart was elaborated that allows the study of time and movements determining the actual productivity. The planned activities were reached through the determination of errors that affect the process by the use of stablished methods like cause - effect diagrams. The design of the Plant and the distribution of the equipment are the principal components for the balance of the lines of production, this the proposal of redistribution of machinery to have a better productivity. Other method that was applied was the inverse diagram to establish the solution of the found errors in the process of jam elaboration, finally an improvement proposal was proposed, for which a layout of the company was made with the old model and improved model that is reflected with the greatest optimization of time and movements, in addition a coding machine of dates of elaboration and expiration was acquired, for the jam containers that are made of glass, which made better the quality and control of the products, opening the possibility of use international regulations in the future.